De moços alegres a LGBTs: explorando memórias e história sobre os homens homossexuais na produção enunciativa dos jornais Folha do Norte e O Liberal (1901-2011) em Belém, Pará - SANTA BRÍGIDA, Jessé Andrade (Universidade Federal do Pará, 2020)
This study aims to explore the enunciations and enunciates about homosexuals in Belém, Pará, published on Folha do Norte and O Liberal newspaper between 1901 and 2011, to understand the memories about these social subjects in the city. We believe that this research is relevant in view of the current moment in which many social subjects seek self-affirmation by the means of rights. Due to the long time span this study covers, we collected data jumping ten to ten years and paying attention to three main events: Carnival, Festa da Chiquita Bacana (a local party) and Belém LGBT Pride Parade. We chose these events based on a bibliographic survey that indicated they were more likely to present enunciations about homosexuals. Thus, we selected issues from February and/or March (Carnival), August and September and/or October (Festa da Chiquita Bacana and LGBT Pride Parade), observing seven issues during the week in which the events took place. When we did not find texts about homosexuals in a particular year, we observed the following year, so as not to let any decade uncovered. Overall, we observed 18 years and 147 issues. From this, we collected 53 texts, 12 from Folha do Norte and 41 from O Liberal, which addressed homosexuals explicitly or implicitly. We also interviewed three male homosexuals between 50 and 70 years old, who live in Belém since 1960, to help us contextualize the sociability and history of homosexuals in Belém. We discussed and presented the data exploring six categories: a) from “moços alegres” (cheerful young man) to transvestites; b) Homosexuals, gays and LGBTS; c) Emphasis on the enunciation; d) Homosexuality and religion; e) Carnival stories; and, f) The movie Giselle. The data indicates that enunciates about homosexuals from early 20th century to mid-1930s were built around the idea of wilderness and bestiality. Meanings related to party, happiness and carnival crossed the time span covered by the research, which is an evidence that the memories about homosexuals were linked to enunciates of moços alegres¸ veado and/or the transvestites. The transvestites were a recurrent image, used by the newspapers as a symbol of male homosexuality. A shift in enunciation was observed in the late 20th century and early of 21st century, when the terms homosexual and LGBT emerged, moving the meanings toward the political actions of the subjects.